1994
DOI: 10.1111/j.1365-2265.1994.tb02573.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased insulin sensitivity in patients with aldosterone producing adenoma

Abstract: Insulin sensitivity was increased in untreated patients with aldosterone producing adenoma. Enhanced insulin receptor binding may contribute to this increased insulin sensitivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 19 publications
(15 reference statements)
0
19
1
Order By: Relevance
“…21 The impairment of insulin secretion and/or sensitivity have been reported in patients with PA, however the reports concerning this topic are contradictory. Ishimori et al 16 found increased insulin sensitivity in patients with PA. On the other hand our recent study 17 and the study of Shamiss et al 14 demonstrated decreased insulin sensitivity in these patients.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…21 The impairment of insulin secretion and/or sensitivity have been reported in patients with PA, however the reports concerning this topic are contradictory. Ishimori et al 16 found increased insulin sensitivity in patients with PA. On the other hand our recent study 17 and the study of Shamiss et al 14 demonstrated decreased insulin sensitivity in these patients.…”
Section: Discussionmentioning
confidence: 97%
“…14 Moreover, a series of authors reported alterations of insulin sensitivity and/or release in patients with this disease, although the results of these studies are contradictory. [14][15][16][17] Recently, Torpy et al 18 demonstrated that serum leptin levels in patients with PA increased after surgical removal of aldosteroneproducing adenoma. The reason for this increase was not clarified by Torpy's study.…”
Section: Discussionmentioning
confidence: 99%
“…64 This supports the view that essential hypertension is associated with increased insulin resistance and hyperinsulinemia and accounts for enhanced cardiovascular risk in these patients. 65 In contrast, an earlier study even reported increased insulin sensitivity in a small sample of patients with PA. 66 Little is known about interactions between aldosterone and insulin signaling at the molecular level. Low K ϩ has been discussed as a pathogenetic factor for disturbed glucose homeostasis in patients with PA, possibly interfering with insulin receptor function, insulin secretion, or gluconeogenesis.…”
Section: Does Elevated Plasma Aldosterone Negatively Influence Msyn Rmentioning
confidence: 99%
“…Clinical features include hypertension, hypokalaemia and metabolic alkalosis. Hyperaldosteronism may alter glucose metabolism through altering insulin secretion, an effect of reduced pancreatic ß-cell intracellular potassium, or altering insulin sensitivity (13,14). Correspondingly, leptin secretion, which is responsive to insulin levels, is reduced in primary aldosteronism and recovers following curative adrenalectomy (15).…”
Section: Dj Torpy Et Almentioning
confidence: 99%